Pengaruh Kualitas Pelayanan, Harga dan Lokasi terhadap Kepuasan Konsumen pada Dealer Honda Sinar Wijaya Motor Kediri - Rahmad Pancipta Sukma; Ahmad Jauhari; Brahma Wahyu Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to ascertain how customer satisfaction at the Honda Sinar Wijaya Motor Kediri dealer is impacted by factors such as location, pricing, and service quality. Quantitative research is what this kind of study is. Primary and secondary data are the methods of data collecting that are employed. At the Honda Sinar Wijaya Motor Kediri Dealer, 77 respondents provided samples for the study through the use of the incidental sampling technique. Literature reviews, interviews, and questionnaires were used to gather the research data. Multiple linear regression analysis is the method of analysis that is employed. The t-test of the service quality variable showed a significant partial influence on customer satisfaction with a sig result of 0.001 <0.05, and the study's multiple linear regression equation was Y = 19,414 + 0.375X1 + 0.521X2 + 0.291X3. With a sig value of 0.001>0.05, price has a strong partial impact on customer satisfaction. With a sig. value of 0.017>0.05, location has a strong partial impact on customer satisfaction. With a significance value of 0.000 <0.05, the F test yielded the F count result. According to the analysis's findings, customer satisfaction at the Honda Sinar Wijaya Motor Kediri Dealer is significantly impacted by pricing, location, and service quality all at the same time.